(untitled) (Studia Iberystyczne, 2019)
Precarious Existence, Implacable Fate: Machado de Assis, Borges and Poe, in Luis Fernando Verissimo Focusing on short stories and novels by Luis Fernando Verissimo, this essay discusses the robust similarities between stylistic and thematic aspects of the Gaúcho author’s writing and those of three masters of the narrative who come from different literary traditions: the United States writer Edgar Allan Poe, the Argentinean Jorge Luis Borges, and the Brazilian Joaquim Maria Machado de Assis. The study explores facets that afford cohesion and critical vitality in Verissimo’s strange and disconcerting writing. His narrative as such employs narrators extremely creative. They not only question human language itself and negotiate symbolic connections and intertwined coincidences between life and art, but also mingle facts and fictions, classic myths mundane deeds, which, quite often, fuse themselves in the midst of the bizarre and the imponderable in daily life.